Permanent Magnet Synchronous Generator Wind Power Plant Study - Celikdemir, Soner; Ozdemir, Mehmet (Ieee, 2019)
In this study, low-power wind plant with permanent magnet synchronous generator designed plants were compared with the results of simulation studies. While the design is made to ensure the operation of the wind turbine at different wind speeds are mentioned selection criteria air ducts and components. In addition, DC voltage, charger and inverter aimed to investigate as a whole. Five wings, horizontal axis, permanent magnet and the output of the rectifier circuit of wind turbine system is described the design steps. The rectifier output voltage, after applying the voltage regulator was charged with battery systems. The charged voltage, applied as input to the inverter operating at different loads were analyzed. In the simulation studies, Matlab / Simulink computer program was used. While all this is done, the priority target; to examine the applicability of the study, is to contribute to the expansion of these systems.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: Wind Turbine; Wind Plant Design; Matlab/Simulink Simulation; Permanent Magnet Synchronous Generator